1997
DOI: 10.1163/156853997x00016
|View full text |Cite
|
Sign up to set email alerts
|

Experience in Substrate-Enriched and Substrate-Impoverished Environments Affects Behaviour of Pigs in a T-Maze Task

Abstract: Previous research showed that pigs reared in substrate-impoverished conditions performed a smaller proportion of their total behavioural repertoire in their home pens (showed lower behavioural diversity), than pigs reared in substrate-enriched conditions. This study examined whether these differences were the result of fundamental changes in behavioural organisation. A T-maze task was used to test the hypothesis that substrate-impoverished pigs are prone to develop fixed, unvarying behaviour which may underlie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
3
16
1
Order By: Relevance
“…B pigs showed more nosing behaviour during exploration trials than E pigs. This agrees with other studies reporting an increased exploration of novel environments or objects in pigs from barren housing, and has been attributed to an unsatisWed motivation for exploration in their home environment (Mendl et al 1997a;De Jong et al 1998;Olsson et al 1999;Bolhuis 2004).…”
Section: Exploration Trialssupporting
confidence: 92%
“…B pigs showed more nosing behaviour during exploration trials than E pigs. This agrees with other studies reporting an increased exploration of novel environments or objects in pigs from barren housing, and has been attributed to an unsatisWed motivation for exploration in their home environment (Mendl et al 1997a;De Jong et al 1998;Olsson et al 1999;Bolhuis 2004).…”
Section: Exploration Trialssupporting
confidence: 92%
“…As earlier demonstrated for pigs reared in enriched environments (Mendl et al, 1997;Johnson et al, 2001;Gentry et al, 2002b), outdoor pigs were more active and showed a larger range of activities than indoor pigs. The absence of feeding or grazing behaviour, reaching between 20 and 40% of observations in outdoor pigs under certain conditions (Stern and Andresen, 2003), is explained by the absence of grass or other feeding substrates in the present experiment.…”
Section: Discussionsupporting
confidence: 67%
“…Taking into account these results, it could also be that female pigs have a higher motivation to explore novel stimuli or are less fearful (Brown et al, 2009). The latter is supported by results of the novel environment test in which female piglets expressed less fear-related behaviors than male piglets, such as high-pitched vocalizations (e.g., Düpjan et al, 2008) and urinating and defecating (Mendl et al, 1997). Also Chaloupková et al (2007) found that castrated male piglets squealed more than female piglets in an individual novel environment test.…”
Section: Gender Differencesmentioning
confidence: 85%
“…This result is consistent with Jansen et al (2009), who found HR pigs to be more active (i.e., running and walking) than LR pigs in a novel maze test. To be socially isolated is very stressful for a piglet (Kanitz et al, 2009), which was also visible from the behavior (e.g., standing alert, defecations, and urination; Boissy, 1995;Mendl et al, 1997) of piglets in the test. From these studies, it can be concluded that the response of a piglet in the backtest seems to be predictive of its response in tests later in life when those tests are sufficiently novel and challenging for the pig, but for other tests the backtest has limited predictive value.…”
Section: Social Breeding Value For Growth and Backtestmentioning
confidence: 99%